Growth of sandfish (Holothuria scabra Jaeger) in and earthpond - Bulseco, Renz Marione Metran
Growth in juvenile Holothuria scabra in an earrthpond was investigated and correlated with temperature and salinity, Total Organic Matter (TOM), and grain-size. Two trials were conducted: in january-May and November-December of 2010. Twenty juveniles were introduced onto five 1m x5m pens which were laid out in a marine earthpond. Water temperature and salinity were recorded by a water logger.
Thesis, Undergarduate (B.S. Biology)-U.P. Mindanao
Keywords: Holothuria scabra; Earthpond; Sediments; Total Organic Matter (TOM); Salinity; Juvenile Holothuria scabra; Sandfish; Sea cucumbers